Effects of Kersen Juice and Lakum Leaf Extract on Lipid Profile of White Rats With Hyperlipidemia - Didin Sopandi; Tyas Rini Saraswati; Enny Yusuf Wachidah Yuniwarti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Kersen fruit and Lakum leaf contain substances that are potential as an antihyperlipidemic. The aim of this research was to analyze the effects of Kersen juice (Mutingia calabura L.) with dosage 0.2 ml/200 g BW andÂ lakum leaf extract (Cayratia trifolia L.) with dosage of 40 mg/200 g BW on lipid profile of white rats (Rattus norvegicus L.) with hyperlipidemia. This study used a Complete Randomized Design (CRD). This study used twenty adult male Wistar rats which were divided into five groups : P0 as a control group, P1 as a High Feed Diet (HFD) control group, P2 as a HFD group treated with Kersen juice with dosage of 0.2 ml/200 g BW, P3 as a HFD group treated with Lakum leaf extract with dosage of 40 mg/200 g BW and P4 as a HFD group treated with simvastatin. The treatments were given orally for 28 days. The parameters of this study were the level of cholesterol, HDL, LDL and triglyceride, as well as body weight, and food consumption. One-way ANOVA test was performed to determine the significant differences p0.05 between groups followed by Duncan test with a 95% significant level. The results showed that compared to Kersen juice with dosage of 0.2 ml/200 g BW, administration of Lakum leaf extract with dosage of 40 mg/200 g BW was more effective in lowering cholesterol level, triglyceride and increasing HDL level, however, they were not effective in lowering LDL in rats with hyperlipidemia. This result shows that kersen and lakum leaf could be an alternative to prevent and avoid further effects of high cholesterol in people with hyperlipidemia.